CO2-abatement cost of residential heat pumps with active demand response: demand- and supply-side effects. (15th October 2015) - Patteeuw, Dieter; Reynders, Glenn; Bruninx, Kenneth; Protopapadaki, Christina; Delarue, Erik; D'haeseleer, William; Saelens, Dirk; Helsen, Lieve
Highlights: The CO2 -abatement cost of residential heat pumps is determined in a future setting. The impact on electricity generation is considered via an integrated model. Multiple building and heating system cases are modeled and compared. Active demand response contributes significantly in lowering CO2 -abatement cost. Great reductions are achieved in CO2 emissions, curtailment and peak generation. Abstract: Heat pumps are widely recognized as a key technology to reduce CO 2 emissions in the residential building sector, especially when the electricity-generation system is to decarbonize by means of large-scale introduction of renewable electric power generation sources. If heat pumps would be installed in large numbers in the future, the question arises whether all building types show equal benefits and thus should be given the same priority for deployment. This paper aims at answering this question by determining the CO 2 -abatement cost of installing a heat pump instead of a condensing gas boiler for residential space heating and domestic hot-water production. The electricity system, as well as the building types, are based on a possible future Belgian setting in 2030 with high RES penetration at the electricity-generation side. The added value of this work compared to the current scientific literature lies in the integrated approach, taking both the electricity-generation system and a bottom up building stock model into account. Furthermore, this paper analyzes the possible benefits of active demand response in this framework. The results show that the main drivers for determining the CO 2 -abatement cost are the renovation level of the building and the type of heat pump installed. For thoroughly insulated buildings, an air-coupled heat pump combined with floor heating is the most economic heating system in terms of CO 2 -abatement cost. Finally, performing active demand response shows clear benefits in reducing costs. Substantial peak shaving can be achieved, making peak capacity at the electricity generation side superfluous, hence lowering the overall CO 2 -abatement cost.